2006
DOI: 10.1103/physreva.74.012708
|View full text |Cite
|
Sign up to set email alerts
|

Absolute total cross-section measurements for electron collisions with tetrahydrofuran

Abstract: The absolute total cross section ͑TCS͒ for electron collisions with tetrahydrofuran C 4 H 8 O in the gas phase has been measured using the linear transmission technique within 1 -370 eV energy range. The total cross section function for e − -C 4 H 8 O collisions is characterized by the relatively high magnitude and the broad enhancement spanned between 4 and 12 eV, with some resonantlike structures. This enhancement can be explained as a result of overlapping core-excited resonances. At higher collision energi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
43
2

Year Published

2006
2006
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(56 citation statements)
references
References 34 publications
11
43
2
Order By: Relevance
“…The results are very well compatible with the value of 5.5Å 2 obtained by Dampc et al [17] at 7 eV. The total cross sections obtained as the sum of the elastic and VE cross sections are about 10% lower than the total cross sections of Możejko et al [13]-a satisfactory agreement in view of the fact that the present cross section does not include electronic excitation, the uncertainty of the visual extrapolation below 10…”
Section: Angle-integrated Cross Sectionssupporting
confidence: 81%
See 1 more Smart Citation
“…The results are very well compatible with the value of 5.5Å 2 obtained by Dampc et al [17] at 7 eV. The total cross sections obtained as the sum of the elastic and VE cross sections are about 10% lower than the total cross sections of Możejko et al [13]-a satisfactory agreement in view of the fact that the present cross section does not include electronic excitation, the uncertainty of the visual extrapolation below 10…”
Section: Angle-integrated Cross Sectionssupporting
confidence: 81%
“…Zecca et al [12] and Możejko et al [13] measured the absolute total cross section for electron scattering by gas-phase THF (Zecca et al reported also the positron cross section). The elastic differential cross section (DCS) at 20 eV and above was measured by Milosavljević et al [14].…”
Section: Introductionmentioning
confidence: 99%
“…The reason for this unanticipated behaviour might lie in the fact that we employed different absorption potentials in our atomic optical models for positron and electron scattering. Note that the present measurements and the electron TCS from Możejko et al 23 do merge at around 130 eV as expected. This suggests that further development of our IAM-SCAR approach is warranted, particularly, perhaps, in the positron case.…”
Section: A Total Cross Sectionssupporting
confidence: 68%
“…In particular, we note the total cross section (TCS) measurements of Zecca et al, 22 Możejko et al, 23 and Baek et al 24 Elastic differential cross section (DCS) measurements at selected impact energies have been carried out by Milosavljević et al, 25 Allan, 26 Colyer et al, 27 Dampc et al, 28 Gauf et al, 29 and Baek et al 24 Except for the work of Milosavljević et al, 25 these groups also reported elastic integral cross sections (ICS). To the best of our knowledge, the only electron-impact, discrete electronic-state excitation cross sections are those of Do et al, 30 while a review of all the available earlier work and a recommended database for electron-THF scattering can be found in Fuss et al 31 Among the theoretical studies on electron-THF scattering, we note the TCS calculation using the R-matrix method of Bouchiha et al 32 Computations of the elastic DCS have been reported by Możejko and Sanche 33 with the independent atom model (IAM), Trevisan et al 34 using the complex Kohn variational method, and Winstead and McKoy 35 and Gauf et al 29 both employing the Schwinger multichannel method (SMC).…”
Section: Introductionmentioning
confidence: 99%
“…These include measurements of elastic DCSs for THF, [11][12][13][14] THFA, 15 and 3HTHF. 16,17 Total cross sections for electron and positron scattering from THF, [18][19][20] 3HTHF, 21 and THFA (Refs. 22 and 23) have also been measured.…”
Section: Introductionmentioning
confidence: 99%